Casuistic cases of migration of the intrauterine device - Н. В. Косей; О. А. Гюльмамедова; Н. М. Євтушенко (Publishing House TRILIST, 2018)
The purpose of this article is to provide information of isolated cases of migration of intrauterine contraceptive devices (IUD), familiarity with them will be useful in medical practice. In analyzing the medical literature related to the migration of the IUD, a large range of ectopic spirals and a variety of clinical manifestations attract attention. Usually setting the IUD is not difficult. However, complications can sometimes occur: infection, uterine bleeding, ectopic pregnancy, and uterine perforation. This does not happen very often, but at the same time there are potentially serious complications. In cases of complete perforation, the IUD may migrate to various intra-abdominal structures. Thus, according to the analysis of medical literature, most often the IUD migrates into the greater omentum (26.7%), Douglas space (21.5%), the lumen of the colon (10.4%), myometrium (7.4%), wide ligament of the uterus (6.7%), abdominal cavity (5.2%), small intestine (4.4%), large intestine (3.7%), bladder, groin, ovaries, fallopian tubes. Women with chronic pelvic pain on the background of an established IUD should be carefully examined for possible uterine perforation or intrauterine migration. In the differential diagnosis of the causes of pain syndrome, the main role is played by ultrasound examination and hysteroscopy, which allows you to accurately determine the position of the IUD in the uterus or outside it. However, in cases of partial migration, additional clarifying diagnostic methods are used. Computed tomography is effective for determining the location of the IUD, its relationship with neighboring structures, and allows to evaluate other possible causes of dysfunction of the urinary tract. All modern IUDs are radiopaque, therefore, to determine their localization is also used survey X-ray. The range of methods for extracting migrated IUDs is quite diverse, but endoscopic techniques are priorities. Despite the contradictory views on the management of women with an ectopic arrangement of the IUD and the absence of any symptoms, all ectopic contraceptives should be removed as soon as possible after the diagnosis, taking into account the type and localization of the IUD.